THE EFFECT OF USING CONSTRASTIVE METHOD IN TEACHING ENGLISH NOUN PHRASES - Sihabuddin, Sihabuddin (UNDIKMA Mataram (Eks. IKIP Mataram), 2019)
The aim of this study was to find out the effect of contrastive method toward students? English noun phrases ability, the reflection of students comprehension toward the phrases and the students? perception toward the method in teaching English noun phrases. The object of this study was students at MTS Negeri 3 Mataram grade VIIIA. This study was quasi-experimental that applied mix method: quantitative and qualitative research method. The instruments for collecting data in this study were a test, questionnaire, and interview guide. The result of this study showed that the method had a positive effect on students? ability in constructing English noun phrases, and the preception of the students toward the method was positive as well. The method affects the students' ability in constructing English noun phrases correctly.